Estimation of Rooftop Rainwater and Solar Power Harvesting Potential at University Campus using Remote Sensing and GIS Techniques - Thakur, Kriti; Aggarwal, R. K.; Agnihotri, Deepak; Agrawal, Ghanshyam (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during 2023 at Dr. Y. S. Parmar University of Horticulture & Forestry, Nauni, Himachal Pradesh, India to study rooftop rainwater and solar power harvesting potential at Nauni using GIS techniques. Universities consumed large quantities of water and energy, often sourced externally or from non-renewable resources, which contributed to environmental impacts and financial costs. Around 151 university buildings were digitized to estimate the harvesting potential. The total rooftop area of 8,318 m2 was estimated. The digitized rooftop area was verified manually with an accuracy of 99%. The digitized area and the actual area of the buildings were compared, and the error efficiency of the buildings was calculated. The estimated annual rooftop rainwater harvesting potential was 42,919.24 m3, whereas the total water consumption of the university campus was 154.22 m3 day-1 and 56,291.77 m3 year-1. The harvested rainwater was sufficient to fulfil 76% of the water needs and 60% of the basic needs of drinking and cooking at the university. The Digital Elevation Model and topographic maps of the campus were prepared to estimate the solar power potential. The south-facing rooftop area was estimated to be 20261.4 m2. This area was capable of generating daily solar power of 2026.4 kW. The annual rooftop solar potential was estimated to be 2269 MWh, which could fulfil 99.59% of the electricity requirement of the university.